Effect of Carbon Supported Pt Catalysts on Selective Hydrogenation of Cinnamaldehyde - Qing Han; Yunfei Liu; Dong Wang; Fulong Yuan; Xiaoyu Niu; Yujun Zhu (Journal of Chemistry)
Selective hydrogenation of cinnamaldehyde (CAL) to cinnamyl alcohol (COL) is of both fundamental and industrial interest. It is of great significance to evaluate the possible differences between different supports arising from metal dispersion and electronic effects, in terms of activity and selectivity. Herein, Pt catalysts on different carbon supports including carbon nanotubes (CNTs) and reduced graphene oxides (RGO) were developed by a simple wet impregnation method. The resultant catalysts were well characterized by XRD, Raman, N2 physisorption, TEM, and XPS analysis. Applied in the hydrogenation of cinnamaldehyde, 3.5 wt% Pt/CNT shows much higher selectivity towards cinnamyl alcohol (62%) than 3.5 wt% Pt/RGO@SiO2 (48%). The enhanced activity can be ascribed to the high graphitization degree of CNTs and high density of dispersed Pt electron cloud.